207k views
0 votes
132=-6+3(1-5p) solve the equation

2 Answers

2 votes

Answer:

p=-9

Explanation:

132=-6+3 (1-5p)

-6+3 (1-5p)=132

-6+3 (1-5p)+6=132+6

3(1-5p)=138

3(1-5p)/3=138/3

1-5p=46

1-5p-1=46-1

-5p=45

p=-9

User Commander
by
5.2k points
6 votes

Answer:


p = -9\\

Explanation:

Step 1: Distribute


132 = -6 + 3(1 - 5p)


132 = -6 + (3 * 1) + (3 * -5p)


132 = -6 + 3 - 15p

Step 2: Combine like terms


132 = (-6 + 3) - 15p


132 = -3 - 15p

Step 3: Add 3 to both sides


132 + 3 = -3 - 15p + 3


135 = -15p

Step 4: Divide both sides by -15


135 / -15 = -15p / -15


-9 = p

Answer:
p = -9\\

User Alessandro Teruzzi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.